2022
DOI: 10.3389/fimmu.2022.1004985
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine reverses neurocognitive impairment in EcoHIV infected mice: A potential therapy for HIV-NCI

Abstract: Thirty-eight million people worldwide are living with HIV, PWH, a major public health problem. Antiretroviral therapy (ART) revolutionized HIV treatment and significantly increased the lifespan of PWH. However, approximately 15-50% of PWH develop HIV associated neurocognitive disorders (HIV-NCI), a spectrum of cognitive deficits, that negatively impact quality of life. Many PWH also have opioid use disorder (OUD), and studies in animal models of HIV infection as well as in PWH suggest that OUD can contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 85 publications
2
8
0
Order By: Relevance
“…5 ), suggest that cells resident in the brain, likely perivascular macrophages and microglia, maintain EcoHIV infection and its pathogenic effects upon cognitive function regardless of potential loss of CCL2 driven monocyte migration to the brain. A collaborative group including some of the coauthors of the present work recently reported that NCI is reversed by treatment of EcoHIV-infected mice with buprenorphine 56 . Buprenorphine treatment also reduced HIV burdens and inflammatory monocyte levels in the brain 56 , suggesting that continuing migration of HIV-infected monocytes to the brain is required to maintain HIV-NCI.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…5 ), suggest that cells resident in the brain, likely perivascular macrophages and microglia, maintain EcoHIV infection and its pathogenic effects upon cognitive function regardless of potential loss of CCL2 driven monocyte migration to the brain. A collaborative group including some of the coauthors of the present work recently reported that NCI is reversed by treatment of EcoHIV-infected mice with buprenorphine 56 . Buprenorphine treatment also reduced HIV burdens and inflammatory monocyte levels in the brain 56 , suggesting that continuing migration of HIV-infected monocytes to the brain is required to maintain HIV-NCI.…”
Section: Discussionmentioning
confidence: 64%
“…A collaborative group including some of the coauthors of the present work recently reported that NCI is reversed by treatment of EcoHIV-infected mice with buprenorphine 56 . Buprenorphine treatment also reduced HIV burdens and inflammatory monocyte levels in the brain 56 , suggesting that continuing migration of HIV-infected monocytes to the brain is required to maintain HIV-NCI. However, since buprenorphine also affects various aspects of behavior 57 , 58 , additional mechanisms may apply.…”
Section: Discussionmentioning
confidence: 64%
“…EcoHIV NCI in mice 54 ; possibly through its action on CCL2 expression 38 . This suggests that buprenorphine reverses NCI through inhibition of monocyte migration, however, buprenorphine also has effects within the brain upon various aspects of behavior 55,56 , so the mechanism of buprenorphine action upon EcoHIV NCI remains under study.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced brain monocyte-induced inflammatory response and reversal of the dendritic injury to the hippocampus and cortex due to buprenorphine might also explain the improvement. Animal studies reported that buprenorphine pretreatment prevents HIV-induced cognitive impairment in mice, and buprenorphine treatment of HIV-NCI (HIV-associated neurocognitive disorder) mice reverses the disease 44,45 . Our patients were on relatively low-dose buprenorphine (7.07 ± 2.92 mg daily).…”
Section: Discussionmentioning
confidence: 95%
“…Animal studies reported that buprenorphine pretreatment prevents HIV-induced cognitive impairment in mice, and buprenorphine treatment of HIV-NCI (HIV-associated neurocognitive disorder) mice reverses the disease. 44,45 Our patients were on relatively low-dose buprenorphine (7.07 ± 2.92 mg daily). Pre-experimental studies showed that low-dose buprenorphine might induce the expression of oligodendrocytes and myelination, further improving plasticity and remodeling.…”
Section: Discussionmentioning
confidence: 99%